Expression and characterization of protein disulfide isomerase family proteins in bread wheat - Kimura, Shizuka (BMC Plant Biol, 2015)
BACKGROUND: The major wheat seed proteins are storage proteins that are synthesized in the rough endoplasmic reticulum (ER) of starchy endosperm cells. Many of these proteins have intra- and intermolecular disulfide bonds. In eukaryotes, the formation of most intramolecular disulfide bonds in the ER is thought to be catalyzed by protein disulfide isomerase (PDI) family proteins. The cDNAs that encode eight groups of bread wheat (Triticum aestivum L.) PDI family proteins have been cloned, and their expression levels in developing wheat grains have been determined. The purpose of the present study was to characterize the enzymatic properties of the wheat PDI family proteins and clarify their expression patterns in wheat caryopses. RESULTS: PDI family cDNAs, which are categorized into group I (TaPDIL1Aα, TaPDIL1Aβ, TaPDIL1Aγ, TaPDIL1Aδ, and TaPDIL1B), group II (TaPDIL2), group III (TaPDIL3A), group IV (TaPDIL4D), and group V (TaPDIL5A), were cloned. The expression levels of recombinant TaPDIL1Aα, TaPDIL1B, TaPDIL2, TaPDIL3A, TaPDIL4D, and TaPDIL5A in Escherichia coli were established from the cloned cDNAs. All recombinant proteins were expressed in soluble forms and purified. Aside from TaPDIL3A, the recombinant proteins exhibited oxidative refolding activity on reduced and denatured ribonuclease A. Five groups of PDI family proteins were distributed throughout wheat caryopses, and expression levels of these proteins were higher during grain filling than in the late stage of maturing. Localization of these proteins in the ER was confirmed by fluorescent immunostaining of the immature caryopses. In mature grains, the five groups of PDI family proteins remained in the aleurone cells and the protein matrix of the starchy endosperm. CONCLUSIONS: High expression of PDI family proteins during grain filling in the starchy endosperm suggest that these proteins play an important role in forming intramolecular disulfide bonds in seed storage proteins. In addition, these PDI family proteins that remain in the aleurone layers of mature grains likely assist in folding newly synthesized hydrolytic enzymes during germination. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-015-0460-2) contains supplementary material, which is available to authorized users.